Desempenho da memória, acesso ao léxico mental e vocabulário em crianças com queixas de aprendizagem - França, Ingrid Jessie Freitas Coutinho (2023)
Learning to read and write does not develop suddenly and instantly, it is considered a stage of great complexity as it demands good cognitive functioning so that there is progression towards the notion of explicit, conscious and reflective knowledge about the language and its utility. The objective of this study was to identify working memory performance, access to the mental lexicon and vocabulary in children who complain of learning difficulties. It is a case series study, descriptive observational, qualitative, in which five individuals with complaints about learning to read and write participated, between 6 and 10 years old of both sexes linked to an extension project called: CUIDAR: Speech therapy assessment in children with learning difficulties and Attention Deficit Hyperactivity Disorder, from the Federal University of Paraíba-UFPB. For the evaluation instrument for collecting data for this research, the following protocols were applied: USP Picture Vocabulary Test (TVFUSP), Children's Naming Test (TIN), Automatic Naming Test (TENA) and Phonological Working Memory Test- not words and digits. The performance and total score of each test were analyzed separately by participant and classified according to the specific standards of the applied protocols. In relation to TENA, cases I, III and V with lower classification, case II below average and case IV within the average on the color, letter and number boards and below average on the object board. In the TIN protocol, cases I, II, III and IV with an average classification and case V with a very low classification. In the TVFUSP protocol, in cases II, III and IV with an average classification, and cases I and V with a very low classification. Regarding the PHONOLOGICAL WORKING MEMORY protocol, cases I, II and III with classification below average and case IV within the average in pseudowords and above the average in digits and case V within the average in pseudowords and below average in digits. It was possible to identify that all participants indicated a deficit in the skills assessed in the study, not presenting a score within the expected range for their age and school grade, with the majority being classified as inferior. With regard to memory, it was also found that the majority of participants in this research presented a performance below average, which shows that this ability is also lagging behind and signaling risk factors in these individuals. In relation to vocabulary, there was variability between participants, with only the child in clinical case IV having a very low classification, thus indicating that this individual has a relevant deficit in their vocabulary, while the other patients performed within the average.